The stability evaluation of clay tunnels via the non-linear deterioration of physical and mechanical properties of surrounding rocks - Huang, Jun; Liu, Xingwang; Ma, Zongyuan; Lv, Gao; Dang, Kangning (Frontiers in Earth Science, 2023)
Simple, fast, and reliable methods for the stability evaluation of tunnels can facilitate the construction and development of tunneling projects. The problems related to tunnel stability at this stage can be well analyzed via theoretical analysis method, model test method, or numerical analysis method. On the other hand, those methods are hard to be effectively analyzed these projects with higher importance, shorter decision and design period, and more urgent construction period. This paper proposed research works on the stability evaluation of clay tunnels. Firstly, a state function with the variables of stress and strain state is presented to predict the stress and strain states of surrounding rocks caused by tunnel excavation, which characterize the physical-mechanical state of surrounding rocks (also called stability state). Secondly, the nonlinear deterioration of the physical and mechanical properties of surrounding rocks will be simulated, and the expressions and calculation methods of the tunnel stability reserve factor will be yielded. Finally, the results of the proposed method were compared with the strength reduction method and the limit equilibrium method with a clay tunnel example. The comparison between the three feature points of the arch crown, sidewall, and arch bottom showed that the stability reserve factor of the clay tunnel was smaller than those of the strength reduction method and the limit equilibrium method. The values of limit displacement obtained by the proposed method were closer to the field monitoring data than that of the strength reduction method. Therefore, this study could be better applied to the stability evaluation of clay tunnels.